국내 배터리 3사(LG에너지솔루션, 삼성SDI, SK온)의 지속가능한 광물자원 확보 전략 - 권성구(Seongku Kwon); 한수호(Suho Han); 박준희(Junhee Park); 조유라(Yoora Cho); 이재혁(Jay Hyuk Rhee); 옥용식(Yong Sik Ok ) (Daehan hwan'gyeong gonghag hoeji, 2024)
최근 들어 국제적으로 지속가능성 이슈가 부각되고 환경 규제가 증가함에 따라 국내 기업의 지속가능경영에대한 필요성이 증가하고 있다. 본 연구에서는 지속가능한 광물 채굴과 조달에 대한 국내 배터리 3사(LG에너지솔루션, 삼성SDI, SK온)의 대응 현황을 평가하고자 광물 공급 과정에서의 환경 관리 현황을 분석하였다. 특히, 기업은이러한 규제에 전략적으로 대응하여 경영 전략을 수립할 필요가 있으므로 경영학적인 관점에서 지속가능한 광물자원 확보를 위한 전략을 제안하였다. 그 결과, 기업은 광물 자원 확보 전략에 대해 중장기적인 성과 측정이 필요한 것으로 판단되었다. 즉, 광물은 채굴단계부터 활용단계의 공급사 평가 시, OECD 가이드라인을 뛰어 넘는 보다적극적인 환경관리 계획을 수립해야 할 것이다. 또한 공급망 관리 측면에서는 온실가스 배출 모니터링 이외에도토양 및 수질오염, 폐기물관리, 생물다양성의 손실에 대한 평가가 요구된다. 끝으로 국내 배터리 기업은 탄력적인배터리 공급망을 구축할 수 있도록 안정적인 폐배터리 재활용 시스템을 구축해야 할 것이다. The proliferation of global regulations concerning sustainability and environmental protection poses a significant challenge to maintaining corporate sustainability. Consequently, companies must strategically respond to navigate these regulations in their management plans. The objective of this research was to analyze how Korean companies(LG Energy Solution, Samsung SDI, SK On) are responding to sustainable mining and procurement and how they adopt environmentally friendly practices in their mineral supply chain for battery manufacturing. We also proposed new actions to enhance their management strategies for sustainable mineral resource management. Our observations indicated that companies should implement a long-term performance measurement throughout their mineral supply chain. Additionally, there is an urgent need to develop a more proactive environmental management plan when evaluating suppliers from mineral extraction to utilization, adhering to global guidelines such as OECD regulation. In addition to the widely adopted monitoring of greenhouse gas emissions, priority assessments must be undertaken concerning soil and water pollution, waste management, and biodiversity loss within the supply chain linked with climate change under the nature-positive concept. We recommended the establishment of a recycling system for battery waste(i.e., minerals), which is essential for a resilient battery supply chain. KCI Citation Count: 0